Living and learning: Strategies for survival in a literate world - Juliet Merrifield; Mary Beth Bingman (Adult Education Research Conference, 1993)
Adults with low literacy skills have developed strategies to deal with literacy demands and to learn in their everyday lives. This qualitative research project profiled living and learning by twelve diverse adults.